Bis(acetylacetonato-κ(2) O,O′)aqua(diacetylmethanido-κC)iridium(III) - Chang, Qiao-Wen (International Union of Crystallography, 2009)
In the crystal structure of the title compound, [Ir(C(5)H(7)O(2))(3)(H(2)O)], the Ir(III) atom is six-coordinated and situated in a slightly distorted octahedral environment. The complex contains both Ir—O and Ir—C bonds and was isolated from a reaction mixture of IrCl(3)(H(2)O)(x), pentane-2,5-dione and NaHCO(3). O—H⋯O hydrogen bonding between the water molecules and the carbonyl O atoms of adjacent molecules leads to a layered motif extending parallel to (010).